(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Since grammar instruction supports the foundational aspects of young learners’ linguistic development, many linguists value its importance. The manner of teaching grammar also stirs up a variety of beliefs. It causes confusion on how to teach grammar to young students. Thus, the purpose of this paragraph is to further explore the methods used to teach grammar to young students. It was discovered that the teachers tended to clearly teach grammar after conducting in-depth interviews with the teachers who were observed in the sixth-grade English lessons. It occurred because they saw early on the importance of mastering grammar. Additionally, they believe the students to be mature enough to understand grammatical rules because their reasoning is superior to that of their junior peers.